Sleep Apnea Syndrome in an Elderly Population Admitted to a Geriatric Unit: Prevalence and Effect on Cognitive Function - Attier-Zmudka, Jadwiga; Sérot, Jean-Marie; Valluy, Jeremy; Saffarini, Mo; Douadi, Youcef; Malinowski, Krzysztof Piotr; Balédent, Olivier (Frontiers in Aging Neuroscience, 2020)
Background Sleep apnea leads to cognitive impairment in older patients, but its association with neurodegeneration remains controversial, and most studies do not distinguish between the more common obstructive form (OSAS) and the rarer central form (CSAS). Objective The purpose of this study was to assess the prevalence of the different forms of sleep apnea in a cohort of cognitively impaired elderly patients (>70 years) and to investigate their associations with cognitive deficit, weighted against known risk factors for neurodegeneration. Methods Overnight polygraphy was performed for 76 consecutive patients admitted to our geriatric unit. Their cognitive function was assessed using the Mini Mental-State Exam (MMSE), Mattis Dementia Rating Scale (MDRS) and Stroop test. Multivariable analyses were performed to determine associations between cognitive function and independent variables describing demographics, sleep apnea measures, and cardiovascular risk factors. Results The cohort comprised 58 women and 18 men aged 84 years (range, 73–96). Sleep apnea syndrome was diagnosed in 48 patients (63%), of which 31 (41%) with OSAS and 17 (22%) with CSAS. Multivariable regression analysis revealed that MDRS was lower in patients with OSAS (β=-10.03, p=0.018), that Stroop Colors and Words delays increased with AHI (β=0.17, p=0.030 and β=0.31, p=0.047) and that that Stroop Interference delay was higher in patients with CSAS (β=24.45, p=0.002). Conclusion Sleep apnea is thus highly prevalent in elderly patients with cognitive impairment. OSAS was associated with lower general cognitive function, while CSAS was only associated with increased Stroop Interference delays. Elderly patients with cognitive deficit could benefit from sleep apnea screening and treatment.